Identifying Pupils’ Mental Model of the Day and Night Concept - Parlina, T. Aci; Hermita, Neni; Alpusari, Mahmud; Noviana, Eddy (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
Many students and even teachers still cannot recognize the relevance of the model to build physical knowledge. The study of mental representations built by students in their interactions with the world, phenomena and artifacts, is an important line of research in science education. Therefore, it is not surprising that analogies play an important role inscience education, because the construction of students in mental models of abstractphenomena must be rooted in some existing or previous experiences, to interpret more complex ideas. The purpose of this study is to investigate mental models elementary school students against the phenomenon of day and night. This research is quantitativedescriptive. The research subjects were 20 students in grade six. The results showed that 20% of students had a low mental model (LMM), 45% of students had a moderate mental model (MMM), and 35% of students had a high mental model (HMM). Based on the results of the study it can be said that, (1) 20% of students cannot explain the concepts scientifically and students' understanding is at the level of symbolic representation. (2) 45% of students cannot explain the causes of a phenomenon, student understanding is at the level of macrocospic representation, (3) and 35% of students have concepts with understanding based on real-life observations with scientific concepts learned at school and students' understanding is at the level of representation of microcosms.